The effectiveness of brief solution-focused couple therapy (BSFCT) on reducing couple burnout - Reza Davarniya; Kianoush Zahrakar; Ali Mohammad Nazari (Gonabad University of Medical Sciences, 2018)
Brief solution-focused therapy is a collaborative and non-pathological approach for therapy emphasizing on finding the solution by the client with the help and collaboration of the therapist. The research was conducted to examine the effectiveness of brief solution-focused couple therapy in reducing couple burnout among women. The present research has been conducted by a semi-experimental method with a pretest-posttest and follow-up with control group design. The population of the present research included all the women who visited three counseling centers of the welfare organization and also mental helpers. After the initial screening, 30 women, whose scores were the highest in couple burnout questionnaire were selected as the study sample, and they were assigned into two experimental and control groups (15 participants per group). The data were gathered by Pines's couple burnout measure. The level of couple burnout was measured for the experimental and control group participants before experimental intervention (brief solution-focused couple therapy). Afterwards, the experimental group received the brief solution-focused couple therapy for 7 sessions of 1.5-hour in groups, but the control group received no intervention. Also, the experimental group participated in a follow-up session approximately 5 weeks after the last therapy session. Results showed that brief solution-focused couple therapy has been able to significantly reduce couple burnout in the posttest stage and in the follow-up stage. Brief solution-focused couple therapy can be used for reducing marital problems among couples.